Penyebab Penyakit Layu pada Tanaman Semangka di Karawang, Jawa Barat - Kartini Budiastuti; Efi Toding Tondok; Suryo Wiyono (Jurnal Fitopatologi Indonesia, 2012)
Wilt disease of watermelon is an important disease in Indonesia, but determination of the causal agent has not been reported yet. Postulat Koch based approach was conducted to determine the pathogen causing wilt of watermelon from Karawang, West Java. Fungi associated with wilt symptoms were isolated from stem and root, then the fungal colonies were identified based on their morphological characters. Pathogenicity tests were performed using soil media and wet paper. Host range study involved other Cucurbitaceae plants, i.e. cucumber, melon and paria. Three species of Fusarium were successfully isolated from plants showing wilt symptom, i.e. F. oxysporum, F. solani, and F. semitectum. The fungus F. oxysporum consistently caused the most severe wilt symptom on watermelon, but developed no symptom on other tested cucurbits. The two fungi, F. solani and F. semitectum, caused necrotic on roots and stem of watermelon followed by wilting of the plant. The symptom was different than those of the initial symptoms from the field. Therefore it concluded that wilt symptom of watermelon is caused by Fusarium oxysporum f.sp. niveum. Key words: Cucurbitaceae, Fusarium oxysporum f.sp. niveum, species identification, wilt